Does polycystic ovary syndrome affect morphokinetics or abnormalities in early embryonic development? - Minh Tam Le; Trung Van Nguyen; Tung Thanh Nguyen; Thai Thanh Thi Nguyen; Tam An Thi Nguyen; Quoc Huy Vu Nguyen; Ngoc Thanh Cao (Elsevier, 2019)
Objectives: This study aimed to investigate whether oocyte retrieval from PCOS patients affects the morphokinetics or the incidence of abnormalities in early embryonic development, using time-lapse imaging analysis. Methods: This was a prospective study in total of 39 PCOS patients and 67 women with normal ovarian function, underwent a GnRH antagonist protocol of controlled ovarian stimulation and fertilization by ICSI. 402 zygotes from the PCOS group and 449 zygotes from the control group were observed by time-lapse monitoring for 48 h following sperm injection. Results: Patients with PCOS showed a significantly higher number of retrieved oocytes, and a significantly higher number of metaphase II oocytes per cycle than that of the non-PCOS group (18.85 ± 9.41 vs. 11.48 ± 5.51 and 14.97 ± 7.43 vs. 9.51 ± 4.7, respectively). However, oocyte maturation rate and morphologically assessed embryo quality did not differ between two groups. After 48 h of the embryo culture using time-lapse video recording, most of the embryos in both groups had reached the 4-cell stage (353/449 vs. 314/402 embryos). There were no significant differences between the control and PCOS group regarding the time-points of the successive events in early embryonic development from the appearance of 2 polar bodies to the 6-cell stage. However, the percentage of t2 stages which fell in "optimal range" (>24 h and ≤28 h) was significantly lower in the PCOS group than in the control group (37.8% vs. 48.1%, P = 0.004). The proportion of embryos manifesting abnormal fertility, multinucleation, direct cleavage and reverse cleavage were not significantly different between the two groups. Conclusion: Our data indicated that PCOS does not affect the morphokinetics or incidence of abnormalities in early embryonic development. Keywords: PCOS, Time-lapse monitoring, Morphokinetics, Embryo cleavage, Early development